Tail-Hedge Discounting and the Social Cost of Carbon - Weitzman, Martin L (Journal of Economic Literature, 2013)
The choice of an overall discount rate for climate change investments depends critically on how different components of investment payoffs are discounted at differing rates reflecting their underlying risk characteristics. Such underlying rates can vary enormously, from ≈ 1 percent for idiosyncratic diversifiable risk to ≈ 7 percent for systematic nondiversifiable risk. Which risk-adjusted rate is chosen can have a huge impact on cost-benefit analysis. In this expository paper, I attempt to set forth in accessible language with a simple linear model what I think are some of the basic issues involved in discounting climate risks. The paper introduces a new concept that may be relevant for climate-change discounting: the degree to which an investment hedges against the bad tail of catastrophic damages by insuring positive expected payoffs even under the worst circumstances. The prototype application is calculating the social cost of carbon. (JEL C51, Q54, Q58)